KOMPETENSI AMIL ZAKAT: Studi Mahasiswa Manajemen Zakat dan Wakaf IAIN Tulungagung Menjelang Praktek Pengalaman Lapangan - Supriyadi, Ahmad (El-Barka Journal of Islamic Economics and Business, 2020)
Abstract: Zakat occupies a significant role in Islamic economics. The role of zakat in the history of Islamic civilization is very real and obvious in eradicating poverty and becoming the foundation of the country's economy. In Indonesia the role of zakat cannot be felt widely. This can be seen from the potential that is still being explored, which is 4% of the existing potential of 217 trillion. One of the main problems that occur in Indonesia is the low competence of amil possessed by zakat management institutions in Indonesia. Amil's low competence makes creativity and innovation in zakat institutions very minimal, as a result the collected zakat funds are not optimally utilized to unravel the threads of poverty in Indonesia. The presence of the Department of Zakat Management and Waqf in Islamic Higher Education in Indonesia is an effort to prepare amil’s who are competent in managing zakat. One of the universities that is currently opening the department is IAIN Tulungagung. This study aims to determine the extent of competence of students majoring in Management of zakat and waqf before they conduct Field Experience Practices (PPL).Abstrak: Zakat menduduki peran yang signifikan dalam ekonomi Islam. Peran zakat dalam sejarah peradaban Islam sangat nyata dan kentara dalam memberantas kemiskinan dan menjadi pondasi ekonomi negara. Di Indonesia peran zakat belum bisa dirasakan manfaatnya secara luas. Hal ini bisa dilihat dari masih jauhnya potensi yang tergali yaitu 4% dari potensi yang ada sebesar 217 triliun. Salah satu problem utama yang terjadi di Indonesia adalah rendahnya kompetensi amil pada lembaga-lembaga pengelola zakat di Indonesia. Rendahnya kompetensi amil membuat kreativitas dan inovasi di lembaga-lembaga zakat sangat minim, akibatnya dana zakat yang terkumpul tidak didayagunakan secara optimal untuk mengurai benang kemiskinan di Indonesia. Hadirnya jurusan Manajemen Zakat dan Wakaf di Perguruan Tinggi Islam di Indonesia adalah upaya untuk mempersiapkan amil-amil yang kompeten dalam mengelola zakat. Salah satu Perguruan Tinggi yang saat ini membuka jurusan tersebut adalah IAIN Tulungagung. Penelitian ini bertujuan untuk mengetahui sejauh mana kompetensi mahasiswa jurusan Manajemen zakat dan wakaf sebelum mereka melakukan Praktek Pengalaman Lapangan (PPL).